BINIBINING PARFAITE: A Descriptive Study of the Capsulated Beauty Standards of Young Filipinas - Mendoza, Mary Therese Dominique F. (Animo Repository, 2023)
The study explores the capsulated beauty standards that are present among young Filipinas. It observes how these standards may include having fair skin, sharp facial features, a slim figure, etc. which may be considered foreign-looking. The study also aims to find the influence of foreign countries to the Filipinas' personal preference and definition of beauty and how other countries' beauty standards may become the basis to these Filipinas. The researchers had interviewed a handful of young female students ranging in the age of 18 to 19 years old to determine the features and physical traits that they deem beautiful and possibly how these traits align with various beauty standards. With the gathered information, the researchers intend to make a two-dimensional acrylic painting (solo piece) depicting the comparison between the beauty of the Filipina interviewees as muses and a muse based on the features that they mentioned/a country's beauty standard. Wherein the message is that though both muses look different and have different features, both are still beautiful in their own way.